Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) in Cardiovascular Disease: A Comprehensive Clinical Review on Dilated Cardiomyopathy - Ganipineni, Vijaya Durga Pradeep; Gutlapalli, Sai Dheeraj; Danda, Sumanth; Garlapati, Sameer Krishna Prasad; Fabian, Daniel; Okorie, Ikpechukwu; Paramsothy, Jananthan (Curēus (Palo Alto, CA), 2023)
Dilated cardiomyopathy (DCM) is one of the most important causes of heart failure in developed and developing countries. Currently, most medical interventions in the treatment of DCM are mainly focused on mitigating the progression of the disease and controlling the symptoms. The vast majority of patients who survive till the late stages of the disease require cardiac transplantation; this is exactly why we need novel therapeutic interventions and hopefully treatments that can reverse the clinical cardiac deterioration in patients with DCM. Clustered regularly interspaced short palindromic repeats (CRISPR) technology is a novel therapeutic intervention with such capacity; it can help us edit the genome of patients with genetic etiology for DCM and potentially cure them permanently. This review provides an overview of studies investigating CRISPR-based gene editing in DCM, including the use of CRISPR in DCM disease models, phenotypic screening, and genotype-specific precision therapies. The review discusses the outcomes of these studies and highlights the potential benefits of CRISPR in developing novel genotype-agnostic therapeutic strategies for the genetic causes of DCM. The databases we used to extract relevant literature include PubMed, Google Scholar, and Cochrane Central. We used the Medical Subject Heading (MeSH) strategy for our literature search in PubMed and relevant search keywords for other databases. We screened all the relevant articles from inception till February 22, 2023. We retained 74 research articles after carefully reviewing each of them. We concluded that CRISPR gene editing has shown promise in developing precise and genotype-specific therapeutic strategies for DCM, but there are challenges and limitations, such as delivering CRISPR-Cas9 to human cardiomyocytes and the potential for unintended gene targeting. This study represents a turning point in our understanding of the mechanisms underlying DCM and paves the way for further investigation into the application of genomic editing for identifying novel therapeutic targets. This study can also act as a potential framework for novel therapeutic interventions in other genetic cardiovascular diseases.